(untitled) (Perner’s Contacts, 2022)
The spread of the COVID-19 crisis has had a serious impact on rail carriers due to a significant reduction in demand for rail transport services. Some carriers faced significant liquidity problems, large losses, and in extreme cases, the risk of bankruptcy. During this period, rail passenger transport was particularly affected by the corona crisis. In the first wave of the pandemic, if the curfew was introduced, a large number of train connections on the ŽSR network were canceled and the operation of railway passenger transport was limited to the Saturday mode of operation of the valid timetable. All transport services, especially those provided as services in the public interest, have been reduced to a large extent. Free transportation was also suspended due to the closure of all schools. As a result of these adverse changes, anti-pandemic measures were introduced to reduce the risk of infection during transport. The paper deals with the impact of the COVID-19 pandemic on performance in the public interest in railway passenger transport in Slovakia. The paper describes the proposed system for evaluating anti-pandemic measures affecting mobility in railway passenger transport. The implementation of preventive measures for the next period is proposed to support the operation of railway passenger transport.